The influence of land use systems on soil and surface litter fauna in the western region of Santa Catarina - Bartz, Marie Luise; Brown, George; Orso, Renato; Mafra, Álvaro; Baretta, Dilmar (Revista Ciência Agronômica, 2014)
The aim of this study was to evaluate the abundance of soil and surface litter fauna in the western region of Santa Catarina state, southern Brazil, in the following land use systems (LUS): no-tillage crops (NT), integrated crop-livestock (ICL), pasture (PA), Eucalyptus plantation (EP) and native forest fragments (NF). Sampling was done in three counties in the western region of Santa Catarina: Xanxerê, Chapecó and São Miguel do Oeste, in two seasons (winter and summer). The evaluation of soil/litter fauna in each LUS was performed by installing nine “pitfall traps” per sampling grid (3 x 3). The counties are true replicas. The soil for the chemical attributes was collected at the same sampling points for soil fauna. Altogether, 17 taxa were identified in the five LUS. The presence of groups of fauna was influenced by the type of soil management used. The LUS NF and EP provide better soil conditions for the development of a higher diversity of soil fauna groups compared to other LUS, which showed varying degrees of human intervention, regardless of the sampling season (winter or summer). However, annual crop systems NT and ICL groups showed greater richness and total abundance when compared to the perennial systems (EP and PA). Principal component analysis is an important tool in the study of biological indicators of sustainability because it allows use of soil attributes (chemical and physical) as explanatory environmental variables, which helps in the interpretation of ecological data.